Pengaruh Pengembangan Sumber Daya Manusia Terhadap Kinerja Aparat Pengawasan Intern Pemerintah pada Inspektorat Kabupaten Aceh Barat - Isnaini, Cut Putri; M, Murtaza (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to use a quantitative approach to the phenomena that occur in the Performance of Government Internal Supervisory Apparatus at the Inspectorate of West Aceh Regency. The Data Method used in this study is purposive sampling with a Sample of 50 Employees working at the Inspectorate of West Aceh Regency. The data used are Primary data and Secondary data. The data analysis techniques that will be used are Validity Test, Reliability Test, Classical Assumption Test, Simple Linear Regression Analysis Test, Hypothesis Testing using SPSS22 Software and Determination Coefficient. The results of this test state that the Influence of Human Resource Development has an effect on the Performance of Government Internal Supervisory Apparatus at the Inspectorate of West Aceh Regency.